2009
DOI: 10.1038/nrclinonc.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

An overview of small-molecule inhibitors of VEGFR signaling

Abstract: VEGFR inhibitors are in broad use for the treatment of metastatic renal-cell carcinoma, gastrointestinal stromal tumors and hepatocellular carcinoma and in development in a number of other oncology indications, including colorectal cancer, non-small-cell lung cancer, pancreatic cancer, thyroid malignancies, ovarian cancer, breast cancer and sarcomas. This Review outlines the structure-activity relationships of the 44 VEGFR inhibitors currently in development. An overview of the pharmacokinetic profile of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
233
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(235 citation statements)
references
References 88 publications
1
233
0
1
Order By: Relevance
“…5C). Like VEGFR-1, VEGFR-2 is primarily located on the vascular endothelium, but its expression has also been verified on neuronal, hematopoietic and cancer cells including glioma cells (Knizetova et al, 2008;Ivy et al, 2009). Notably, expression of both, VEGF and VEGFR-2, becomes induced as a consequence of ionizing radiation and is markedly counteracted in response to treatment with CCI-779 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…5C). Like VEGFR-1, VEGFR-2 is primarily located on the vascular endothelium, but its expression has also been verified on neuronal, hematopoietic and cancer cells including glioma cells (Knizetova et al, 2008;Ivy et al, 2009). Notably, expression of both, VEGF and VEGFR-2, becomes induced as a consequence of ionizing radiation and is markedly counteracted in response to treatment with CCI-779 (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Among VEGF receptors, VEGFR-2 is expressed in proliferating vascular endothelial cells of tumours as well as on circulating endothelial progenitor cells, and is related to multiple biological activities of VEGF, such as cell proliferation, migration and survival [3,4]. The EGFR is required for normal cellular proliferation, survival, adhesion, migration, and differentiation but a dysregulation of this pathway can lead to oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…22 Similarly, VEGF signaling and monoclonal antibodies and small molecule inhibitors of VEGF or its receptors have been established as a proven approach to inhibit tumor growth. [23][24][25] In an attempt to elucidate the molecular mechanism underlying the possible tumor vessel promoting activity of stem/progenitor cells, many studies have recently demonstrated that VEGF signaling plays a critical role in the upregulation of a range of cellular functions of EPCs, such as cell migration, proliferation, survival and angiogenesis. 26 In sites of hypoxic tumor tissue, the recruited EPCs secrete abundant VEGF and promote an abnormal vascular network.…”
Section: Resultsmentioning
confidence: 99%